Recommendations for evidence-based endoscopic surgery - Neugebauer,Edmund .; Neugebauer, Edmund A.; Troidl, Hans, 1938-; Sauerland, Stefan; Montori, A. (Alberto). (Paris ; New York : Springer, 2000)
this book have the original recommendations as they were developed by groups of highly respected experts for each topic.
methodology -- laparoscopic hernia repair--diagnosis and treatment of diverticular-- closing remarks and perspectives .
"The updated EAES consensus development conferences.
"European Association for Endoscopic Surgery and other interventional techniques (EAES)"--Cover.
Includes bibliographical references.
All age.
Keywords: Endoscopy -- Therapeutic use -- Congresses; Evidence-based medicine -- Congresses; Endoscopic surgery -- Congresses